ANALISA TOTAL BAKTERI PADA IKAN TUNA ASAP YANG DIRENDAM DENGAN ASAP CAIR â€œWAA SAGUâ€ SELAMA PENYIMPANAN PADA SUHU KAMAR - Esterlina Nanlohy (Program Studi Pendidikan Biologi FKIP Unpatti, 2014)
Backgroud: During this traditional way of preserving fish is usually done by fumigation but is now developed another preservation method that uses liquid smoke method. Method: Liquid smokes used in this study are from the liquid smoke â€œwaa sagoâ€ with concentration 5% + NaCl 5%, soaked 10 minute, the type of fish used tuna (Thunus sp). Meat tuna soaked in liquid smoke and stored for 10 days at room temperature. This study aimed to determine the microbiological quality (total plate count), soaked smoked tuna with liquid smoke